André L. Chevitarese, Gabriele Cornelli e Maria Aparecida de O. Silva (org), A tradição clássica e o Brasil, Brasília, brasil: Editora Fortium, 2008, 212 p. ISBN: 97885-7703-029-3 - Belchior, Mariana Leme (Revista Archai, 2010)
.